2013
DOI: 10.3171/2013.4.spine12345
|View full text |Cite
|
Sign up to set email alerts
|

Upper facet joint en bloc resection for the treatment of thoracic myelopathy caused by ossification of the ligamentum flavum

Abstract: Object The authors introduce a novel technique to treat thoracic myelopathy caused by ossification of the ligamentum flavum (OLF): upper facet joint en bloc resection. This surgical procedure avoids surgery to the most heavily compressed cord surface, contact with the cord, and cord injury. The epidural venous plexus bleeding point can be directly seen and easily controlled during the decompression. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Several authors have reported that the most severe ossification tends to be located at the facet joints 14,[16][17][18] . Several authors have reported that the most severe ossification tends to be located at the facet joints 14,[16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that the most severe ossification tends to be located at the facet joints 14,[16][17][18] . Several authors have reported that the most severe ossification tends to be located at the facet joints 14,[16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional laminectomy and its modifications have gradually been abandoned because they do not completely decompress the spinal cord and can have unsatisfactory final outcomes because of the high early complication rate and recurrence of compression in some patients . Additionally, laminectomy involves some manipulation of the HTHD which, while being insufficient to cause mechanical damage, may interfere with blood supply to the cord .…”
Section: Discussionmentioning
confidence: 99%
“…Upper facet joints en bloc resection was performed as reported previously . In brief, to achieve posterior exposure, the erector spinae were retracted laterally bilaterally, after which posterior decompression was achieved as follows: the spinous processes, inferior facet joints, and laminae of the involved segments were resected, then the bony junction between the pedicle and upper facet joint was detached with a bone rongeur or motor burr via the pedicle‐ossification tunnel.…”
Section: Methodsmentioning
confidence: 99%
“…The neurological deterioration rate after surgery has been reported to be as high as 8.4% (10). The most severe narrowing of the spinal canal was found at the middle level of the facet joints (22,25). At this level, the spinal cord was compressed tightly by the OLF.…”
Section: Surgical Outcomesmentioning
confidence: 99%